Regulation of the Minister of Trade No. 31 of 2023 on E-Commerce Business on the Tiktok Platform: An Analysis of Sharia Economic Law - Nurlinda Nurlinda; Muhammad Dayyan; Zulfikar Daud (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
This study aims to analyze the Regulation of the Minister of Trade Number 31 of 2023 which regulates the use of TikTok as an e-commerce platform from the perspective of Sharia Economic Law. TikTok, which was originally a social media platform, has now transformed into one of the e-commerce platforms that is popular with the public, especially the younger generation. This Regulation of the Minister of Trade provides regulations related to business permits, transparency, and transaction security, which aim to protect consumers and business actors. However, from the perspective of Sharia Economic Law, there are principles such as justice (al-‘adl), balance (al-mizan), and welfare (maqashid syariah) that must be met. This study uses a normative juridical method with an analytical descriptive approach to identify the conformity of these regulations with Sharia principles, as well as the impact of regulations on halal and profitable digital economic activities. The results of the study show that Permendag Number 31 of 2023 is largely in line with the principles of Sharia Economic Law, namely prioritizing aspects of fairness and transaction security, but several points still require further adjustment to be more in line with Sharia values. This study provides recommendations to the government to pay attention to Sharia aspects in the development of digital economic regulations in Indonesia.